DISTRIBUSI LOGAM BERAT PADA AIR DAN SEDIMEN LAUT DI WILAYAH PESISISR KABUPATEN SUMBAWA BARAT - Helmy Akbar; Singgih Afifah Putra; Muhammad Arif Nasution (JURNAL PERIKANAN TROPIS, 2015)
Most of coastal waters of West Sumbawa are wave-exposed areas. As part of Alas Strait this region is located between Lombok and Sumbawa Island. On the land and coastal areas, mineral mining (i.e. gold) activities are operated massively by large private company (i.e. PT. Newmont Nusa Tenggara) and traditional mining by local communities. These activities (especially for traditional mining) are expected to increase the content of heavy metals in the marine and coastal waters surrounding. A residual of mining processing will produce heavy metals disposal. In this study, the distributions of heavy metals (i.e. Hg, Cr6+, Cu, As, Ni, Zn, Pb, and Cd) were measured in the water column and bed sediments of coastal waters of West Sumbawa. This study was conducted during dry season in July 2011. The results show the heavy metal concentrations in water column were mainly within the permissible limits (based on Keputusan Menteri Lingkungan Hidup No. 51, 2004). Except for Cu, the concentration was highest found on most of the stations. The heavy metal contents in bed sediment were low, but varied among sampling points. Furthermore, Cu content in bed sediment also found remarkably high (101,7 mg/Kg) with additionally Zn content was closed (10,6–105,5 mg/Kg) within the permissible limits (based on criteria by Australian and New Zealand Environment and Conservation Council – ANZECC, 2000).